THE INFLUENCE OF THREE MEN IN EDNA PONTELLIER’S LIFE IN THE AWAKENING BY KATE CHOPIN: A Psychoanalytic Study - Ratna Asmarani (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2021)
This paper focuses on the life of Edna Pontellier, the female main character in Kate Chopin’s The Awakening. The purpose is to analyse the influence of the three men in Edna Pontellier’s life. The analysis is done using the concept of id, ego, and superego from Freudian psychoanalysis. The result shows that the first man in Edna Pontellier’s life, Mr. Pontellier/her husband, serves as the superego that always directs Edna’s ego. The second man, Robert Lebrun, is her lover who encourages her to win back her ego which makes her able to begin resisting the superego’s demands. The third man, Alcee Arobin, is the woman-seducer who arouses and fullfils her id in the form of sexual desires which has been repressed so far. However, the psychological conflicts that she has to endure lead to her decision to end her own life in her own way. Key words: id, ego, superego, Freudian psychoanalysis.